Recent advances in electrospun magnetic nanofibers and their applications. Issue 11 (4th March 2022) - Wang, De-Hua; Su, Jie; Liu, Yang-Mo; Yu, Yang; Su, Ying; Xie, Gui-Xu; Jiang, Long-Long; Zhou, Li-Na; Zhu, Dong-Yang; Chen, Si-Heng; Yan, Jia-Shu; Wang, Xiao-Xiong; et al.
Abstract : A review of recent advances in electrospun magnetic nanofibers and their applications Abstract : Magnetism is a classical topic and can be integrated into the new field of nanomaterials easily. Electrospinning is a means of preparing continuous nanofibers, which can be applied for large-scale production of nanomaterials. The preparation of nanofibers by electrospinning technology can take advantage of the fiber membrane and make full use of the huge specific surface area of the nanofiber membrane for catalysis, heat exchange, etc. In this review, three schemes for preparing magnetic materials by electrospinning technology have been summarized to introduce the mainstream electrospinning magnetic material designs. In addition, some analysis techniques for magnetic materials are also introduced, and the typical application fields of magnetic materials are introduced systematically. This work will provide basic knowledge for researchers outside the magnetic field and provide reference for researchers in the nano-field.